RADT-35. CHANGE IN HIPPOCAMPAL VOLUME AS A FUNCTION OF RADIATION DOSE: RESULTS FROM A PROSPECTIVE TRIAL WITH STANDARDIZED IMAGING AND MORPHOMETRIC EVALUATION. (12th November 2021) - Hall, Matthew; Odia, Yazmin; Niazi, Toba; Naidoo, Reshma; Alamdari, Golnar; Kotecha, Rupesh; Tom, Martin; Mohler, Alexander; Wroe, Andrew; Yu, Jen; Von Werne, Katherine; Gallardo, Laura; et al.
Abstract: PURPOSE/OBJECTIVES: MRIs in pediatric and adult brain tumor patients (Age< 35) were prospectively collected at baseline and during follow-up to measure volumetric changes in multiple brain substructures with neurocognitive, laboratory, and quality-of-life assessments. In this planned interim analysis, we model early outcomes for change in hippocampal volume at 6 months following radiotherapy. MATERIALS AND METHODS: As of 5/15/2021, 50 patients enrolled on this prospective study and 41 completed 6-month post-treatment assessments after fractionated intensity-modulated proton therapy. Left and right hippocampus volumes were independently measured on T1 sagittal precontrast MRI at baseline and 6-months after radiotherapy using both automated software and physician-delineated contours. The relationship between mean hippocampus dose and change in volume was assessed by Pearson's correlation coefficient. A linear mixed-effects model was applied to evaluate other predictors associated with change in hippocampal volume, assuming random effects of subjects. RESULTS: Mean hippocampus dose was strongly correlated with change in hippocampal volume at 6 months following radiotherapy (r=−0.727, 95% CI [-0.820, -0.596], p< 0.001). Changes in hippocampal volumes over time were similar between software and physician contours. Hippocampal volume was significantly reduced for mean doses ≥10 Gy (mean Δ -10.8% ± 5.5%, p< 0.001), while no significant volume change was observed with mean doses < 10 Gy (mean Δ +0.7% ± 3.9%). In the mixed-effects model, only mean hippocampus dose was significantly associated with hippocampal volume change (p< 0.001). The final model predicted a -3.4% change in hippocampal volume for every 10 Gy increase in mean dose. CONCLUSIONS: Change in hippocampal volume was correlated with hippocampus mean dose at 6 months following radiotherapy. Future analyses will assess volume change in the hippocampus and other brain substructures over time as a function of radiation dose and correlate with measured neurocognitive and other effects.